Association of NQO2 With UDP-Glucuronosyltransferases Reduces Menadione Toxicity in Neuroblastoma Cells - Chhour, Monivan; Perio, Pierre; Gayon, Regis; Ternet-Fontebasso, Hélène; Ferry, Gilles; Nepveu, Françoise; Boutin, Jean A.; Sudor, Jan; Reybier, Karine (Frontiers in Pharmacology, 2021)
The balance between detoxification and toxicity is linked to enzymes of the drug metabolism Phase I (cytochrome P450 or oxidoreductases) and phase II conjugating enzymes (such as the UGTs). After the reduction of quinones, the product of the reaction, the quinols – if not conjugated - re-oxidizes spontaneously to form the substrate quinone with the concomitant production of the toxic reactive oxygen species (ROS). Herein, we documented the modulation of the toxicity of the quinone menadione on a genetically modified neuroblastoma model cell line that expresses both the quinone oxidoreductase 2 (NQO2, E.C. 1.10.5.1) alone or together with the conjugation enzyme UDP-glucuronosyltransferase (UGT1A6, E.C. 2.4.1.17), one of the two UGT isoenzymes capable to conjugate menadione. As previously shown, NQO2 enzymatic activity is concomitant to massive ROS production, as previously shown. The quantification of ROS produced by the menadione metabolism was probed by electron-paramagnetic resonance (EPR) on cell homogenates, while the production of superoxide was measured by liquid chromatography coupled to mass spectrometry (LC-MS) on intact cells. In addition, the dysregulation of the redox homeostasis upon the cell exposure to menadione was studied by fluorescence measurements. Both EPR and LCMS studies confirmed a significant increase in the ROS production in the NQO2 overexpressing cells due to the fast reduction of quinone into quinol that can re-oxidize to form superoxide radicals. However, the effect of NQO2 inhibition was drastically different between cells overexpressing only NQO2 versus both NQO2 and UGT. Whereas NQO2 inhibition decreases the amount of superoxide in the first case by decreasing the amount of quinol formed, it increased the toxicity of menadione in the cells co-expressing both enzymes. Moreover, for the cells co-expressing QR2 and UGT the homeostasis dysregulation was lower in presence of menadione than for the its counterpart expressing only QR2. Those results confirmed that the cooperation of the two enzymes plays a fundamental role during the cells’ detoxification process. The fluorescence measurements of the variation of redox homeostasis of each cell line and the detection of a glucuronide form of menadiol in the cells co-expressing NQO2 and UGT1A6 enzymes further confirmed our findings.